Utilizing “E-Cooperative” Financial Technology For Business Sustainability (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
The COVID-19 pandemic has had an impact on cooperative business activities. Business management models and mass marketing and direct selling are difficult to implement because of the high risk of spreading COVID-19 through direct interaction. Therefore, innovative efforts are needed so that the cooperative's business is running well so that the sustainability of the cooperative's business is maintained. Utilization of information technology is an alternative to solve the problem impact of the COVID-19 pandemic through the development of e-cooperatives, which are information technology-based media to facilitate virtual cooperative business management. E-cooperative is an alternative that allows the management of cooperatives with less contact. The stages of development are carried out through; identification of requirements/requirements definition, system and software design, implementation and unit testing, integration and system testing, operation and maintenance. The implementation of the e_cooperative application is expected to help manage cooperatives effectively and efficiently and facilitate cooperative management so that it has a positive impact on the business development of members, so that cooperatives and their members can remain productive and carry out economic activities during the COVID-19 pandemic by running a less contact economy. This paper is an introductory paper that forms the basis for research preparation so that research is carried out systematically